1997
DOI: 10.1097/00005344-199709000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Physical Performance is Preserved After Regression of Left Ventricular Hypertrophy

Abstract: Reversal of left ventricular hypertrophy has been shown to improve left ventricular diastolic function in elderly patients with hypertension, but little is known about whether this affects physical performance. Left ventricular mass, cardiac function at rest and during submaximal exercise, and physical performance were assessed in 38 elderly patients with hypertension with left ventricular hypertrophy and normal systolic function before and after 8 and 14 months of therapy with amlodipine or hydrochlorothiazid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…However, results of earlier studies in our laboratory might be less applicable in the present study population that was both considerably older and selected for presence of electrocardiographic LV hypertrophy. In fact, our finding that exercise capacity did not improve during antihypertensive treatment leading to reduction in LV mass is in accordance with results from several other studies, including a Canadian study by Lacourciere et al in elderly hypertensive patients receiving amlodipine or hydrochlorothiazide (12), and a study by Fagard & Lijnen in middle-aged hypertensive patients receiving either hydrochlorothiazide or converting enzyme inhibitor (27), while reduced exercise performance has been reported in young hypertensive patients both during short-term and long-term antihypertensive treatment with atenolol (14,28,29). Of note, population-based nomograms suggest the annular decrease in peak oxygen uptake to be 1.83% (30), which is very close to the actual change found during 1-year follow-up in the present study.…”
Section: Losartan (N524)supporting
confidence: 93%
See 1 more Smart Citation
“…However, results of earlier studies in our laboratory might be less applicable in the present study population that was both considerably older and selected for presence of electrocardiographic LV hypertrophy. In fact, our finding that exercise capacity did not improve during antihypertensive treatment leading to reduction in LV mass is in accordance with results from several other studies, including a Canadian study by Lacourciere et al in elderly hypertensive patients receiving amlodipine or hydrochlorothiazide (12), and a study by Fagard & Lijnen in middle-aged hypertensive patients receiving either hydrochlorothiazide or converting enzyme inhibitor (27), while reduced exercise performance has been reported in young hypertensive patients both during short-term and long-term antihypertensive treatment with atenolol (14,28,29). Of note, population-based nomograms suggest the annular decrease in peak oxygen uptake to be 1.83% (30), which is very close to the actual change found during 1-year follow-up in the present study.…”
Section: Losartan (N524)supporting
confidence: 93%
“…Previous studies have confirmed that sustained blood pressure reduction reduces LV hypertrophy and improves diastolic LV function, but only limited data are available on the influence of LV hypertrophy reduction on exercise capacity in hypertensive patients (11,12). Furthermore, the antihypertensive drug used to lower blood pressure may influence exercise capacity through its individual hemodynamic action.…”
mentioning
confidence: 99%
“…In one study of 38 elderly patients with hypertensive LVH, amlodipine, hydrochlorothiazide or both were administered to reduce blood pressure to normal levels [66]. Along with reduction of blood pressure and LV mass indices, physical performance was well preserved, as measured by exercise capacity.…”
Section: Systolic Performancementioning
confidence: 99%